Cytoskeleton of Bovine Oocytes after Vitrification Using Ethylene Glycol Cryoprotectant - Sri Wahjuningsih (Jurnal Kedokteran Hewan, 2008)
The objective of this research is to know the influence of vitrification method toward thecondition of bovine oocytes cytoskeleton based on microtubules using the immunohistochemistrytechnique. Oocytes classified in two treatments such as fresh oocytes (control) and oocytes withvitrification treatments of 10, 20, 30, 40, and 50% of ethylene glycol (EG). Data were analyzed bydescriptive analyzing. The results of this research indicated that vitrification treatments were affected tomicrotubules organization of oocytes. Concentration of EG 10, 20, 40, and 50% of EG could not repaircytoskeleton after vitrification, but cytoskeleton structure could be protected by EG 30%.